Does shelf preparation have efficacy on immediate loading of 4 implants supporting screw-retained full-arch dental prosthesis - GÖÇMEN, GÖKHAN; ÖZKAN, YAŞAR (My University, 2022)
© 2022 Wolters Kluwer Medknow Publications. All rights reserved.Background: Bone reduction and shelf preparation is a common procedure to establish a new alveolar plane before implant surgery, which might effect the primary stability. Aim: Primary stability was questioned in terms of bone reduction and shelf preparation. The suitability of immediate loading was compared between the implants placed on crests, which underwent alveoloplasty, and the implants placed on a naturally healed alveolar bone. Patients and Methods: We designed and implemented a retrospective cohort study. Twenty patients (mean age 49.2 years) were treated with 160 dental implants. The primary predictor variable was extraction and bone reduction. The secondary predictor variables were bone density and the implant surface. The outcome variables were resonance frequency analysis (RFA) and insertion torque (IT) values. Results: There was no statistically significant difference between groups regarding RFA and IT (P > 0,05). Interactions of surface area with the RFA and IT in both groups were not statistically significant; however, bone density presented a statistically significant effect on outcome variables for both groups. Conclusion: IT and RFA are not influenced by bone reduction, shelf preparation, or the implant surface. Primary stability is mostly affected by bone density in the immediate load of 4 implants to support a full-arch prosthesis.
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Health Sciences; Fundamental Medical Sciences; Klinik Tıp (MED); Klinik Tıp; TIP, GENEL & DAHİLİ; Clinical Medicine (MED); CLINICAL MEDICINE; MEDICINE, GENERAL & INTERNAL; Genel Tıp; General Medicine; Bone reduction; immediate loading; insertion torque; resonance frequency analysis; PRIMARY STABILITY; CORTICAL BONE; EXTRACTION; DENSITY